2017
DOI: 10.1088/1742-6596/938/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

Signals of the double intrinsic heavy quark at the current experiments

Abstract: In this paper we review existing data and analyze experimental opportunities for modern experiments to investigate the signals of intrinsic heavy quarks.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Utilizing this idea, in Refs. [3,4] production of double charmed baryons and the J/ψ meson from the target was investigated at the STAR and LHCb/SMOG fixed-target programs [5,6]. By a straightforward calculation it was shown that in case of the production of intrinsic charm from the target, charm hadrons have a maximum momentum in the laboratory frame of only a few GeV/c and a rapidity y < 2.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing this idea, in Refs. [3,4] production of double charmed baryons and the J/ψ meson from the target was investigated at the STAR and LHCb/SMOG fixed-target programs [5,6]. By a straightforward calculation it was shown that in case of the production of intrinsic charm from the target, charm hadrons have a maximum momentum in the laboratory frame of only a few GeV/c and a rapidity y < 2.…”
Section: Introductionmentioning
confidence: 99%
“…[27] and references therein). Both double J/ψ and doubly-charmed baryons could be produced perturbatively by mechanisms such as double parton scattering or some kind of ladder diagram where e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Note that gluon-gluon fusion, quark-antiquark annihilation and the gluon splitting mechanism of perturbative QCD can explain neither the NA3 cross section nor the x F distribution (see Ref. [27] and references therein). Both double J/ψ and doubly-charmed baryons could be produced perturbatively by mechanisms such as double parton scattering or some kind of ladder diagram where e.g.…”
Section: Introductionmentioning
confidence: 99%